Structural characteristics of the optic nerve head influencing human retinal venous pulsations. (April 2016) - Lam, Jonathan; Chan, Geoffrey; Morgan, William H.; Hazelton, Martin; Betz-Stablein, Brigid; Cringle, Stephen J.; Yu, Dao Yi
Abstract: The relationship between structural characteristics of the optic nerve head and venous pulsations in the human eye remain unknown. Using photoplethysmographic techniques we investigated whether properties of the human retinal veins and their surrounding structures influence venous pulsation. 448 locations of venous pulsation were analysed from 26 normal human eyes. Green channel densitometry derived from video recordings of venous pulsations were used to generate a map of venous pulsation amplitudes along retinal veins. Optical coherence tomography was used to perform quantitative measurements of tissue characteristics at sites of high and low amplitude points as well as in a second analysis, at maximal amplitude pulsation sites from superior and inferior halves of the eyes. Structural characteristics measured included venous diameter, distance from pulsation point to cup margin, vessel length from pulsation point to vein exit, tissue thickness overlying vein, optic disc diameter and presence of a proximal arteriovenous crossing. Increasing venous pulsation amplitudes were associated with larger applied ophthalmodynamometry force, increasing venous diameter, and decreasing absolute cup margin distance (all p < 0.001 ). Increasing distance of maximal amplitude pulsation point to cup margin was associated with the presence of a proximal arteriovenous crossing, increasing venous diameter, and decreasing tissue depth ( all p ≤ 0.001 ). Venous diameter and tissue depth alter venous compliance, which is likely to be a major factor determining sites of venous pulsation. Highlights: Venous pulsation amplitudes and surrounding retinal tissue characteristics were quantified using photoplethysmography and OCT. Larger diameter veins and venous pulsations occurring closer to the optic cup margin have higher pulsation amplitude. The presence of a proximal arteriovenous crossing, venous diameter, and tissue depth affect site of maximal venous pulsation.